Adsorption Removal of Environmental Hormones of Dimethyl Phthalate Using Novel Magnetic Adsorbent. (16th July 2015) - Chang, Chia-Chi; Tseng, Jyi-Yeong; Ji, Dar-Ren; Chiu, Chun-Yu; Lu, De-Sheng; Chang, Ching-Yuan; Yuan, Min-Hao; Chang, Chiung-Fen; Chiou, Chyow-San; Chen, Yi-Hung; Shie, Je-Lueng
Abstract : Magnetic polyvinyl alcohol adsorbent M-PVAL was employed to remove and concentrate dimethyl phthalate DMP. The M-PVAL was prepared after sequential syntheses of magnetic Fe3 O4 (M) and polyvinyl acetate (M-PVAC). The saturated magnetizations of M, M-PVAC, and M-PVAL are 57.2, 26.0, and 43.2 emu g −1 with superparamagnetism, respectively. The average size of M-PVAL by number is 0.75 μ m in micro size. Adsorption experiments include three cases: (1) adjustment of initial pH (pH0 ) of solution to 5, (2) no adjustment of pH0 with value in 6.04–6.64, and (3) adjusted pH0 = 7. The corresponding saturated amounts of adsorption of unimolecular layer of Langmuir isotherm are 4.01, 5.21, and 4.22 mg g −1, respectively. Values of heterogeneity factor of Freundlich isotherm are 2.59, 2.19, and 2.59 which are greater than 1, revealing the favorable adsorption of DMP/M-PVAL system. Values of adsorption activation energy per mole of Dubinin-Radushkevich isotherm are, respectively, of low values of 7.04, 6.48, and 7.19 kJ mol −1, indicating the natural occurring of the adsorption process studied. The tiny size of adsorbent makes the adsorption take place easily while its superparamagnetism is beneficial for the separation and recovery of micro adsorbent from liquid by applying magnetic field after completion of adsorption.